The Political Economy of International Capital Mobility - Watson, M. author. aut Link
XI, 254 p.
Keywords: Matthew Watson draws a distinction between the spatial and the functional mobility of capital, allowing fresh insights into existing work on the subject whilst repoliticizing the very idea of capital being 'in motion'. The dynamics of capital mobility and the patterns of risk exposure are illustrated through four detailed global case studies.